The effect of various supportive housing models on ART adherence among persons living with HIV in supportive housing - Quinn, Katherine (Med Care, 2021)
BACKGROUND: Providing permanent supportive housing to chronically homeless persons living with HIV (PLH) contributes to improved HIV outcomes, including adherence to antiretroviral therapy (ART). This study seeks to understand whether certain components of housing, namely intensity of case management and specialized HIV housing programs, affects ART adherence for persons living with HIV in supportive housing. METHODS: From 2015-2019 we conducted quantitative assessments with 157 persons living with HIV in supportive housing at baseline, 6-, 12-, and 18-months post baseline to identify factors associated with ART adherence. General Estimating Equations for repeated measures were performed to assess bivariate and multivariate measures. RESULTS: Two-thirds of PLH in supportive housing reported 95% or greater adherence to ART. Multivariate analyses indicate that neither intensity of case management services nor specialized housing for PLH were associated with greater ART adherence. Greater time since diagnosis was positively associated with ART adherence. Greater depressive symptoms and African American race were negatively associated with ART adherence. CONCLUSIONS: Study findings reveal that although prior research has established the importance of receipt of housing for homeless PLH, the type or intensity of case management services associated with that housing may not be as important as simply being housed. Our results highlight the importance of considering mental health and more recent HIV diagnosis when developing treatment and case management plans to enhance residents’ ART adherence.